Using Toxic Equivalent Quotients (TEQs) to Evaluate the Risk of Polycyclic Aromatic Hydrocarbons Compounds in Soil at Basrah Governorate, Iraq - Fadya M. Saleem; Hamid T. Al-Saad; Makia M. Al-Hejuje (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2022)
The concentrations of PAHs compounds in this study were estimated in soil of different land uses at Basrah governorate including thirty stations distributed in eight locations (five residential areas, four oil areas, four agricultural areas, five public streets, four petrol stations, two power plants, two public parks and four near private electrical generators). The levels of PAHs compounds mean in all locations ranged from (34.2 - 382.5) ng g-1 dry weight. The means of carcinogenic PAHs compounds in study area varied from (66.4 - 688.8) ng g-1 dry weight and mean of non-carcinogenic PAHs compounds varied from (12.8 - 292.5) ng g-1 dry weight. The carcinogenic PAHs compounds are more dominant than non-carcinogenic PAHs compounds. The human health risk was assessed depending on toxic equivalent quotients (TEQs). The results showed that TEQs ranged from (77.98 - 951.10) ng g-1 dry weight. The TEQs of PAHs in soil samples of oil areas showed the highest level. In general all locations in Basrah governorate were much polluted with PAHs compounds due to urban and industrial development. The present study represents the first study to assess a human health risk due to exposure to PAHs compounds in soil along Basrah governorate.